Sistem Informasi Produksi Pencatatan Bahan Baku pada UMKM Keripik Singkong Metode Material Requirement Planning (MRP) - Nur Anzelina Hrp; Aditya Arielevi; Atfa Abdi Mustofa; Dinda Putri Handika; Marbujing Sari Ritonga; M. Fauzan Arrasyid (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
Micro, small, and medium enterprises (MSMEs) engaged in cassava chips production have significant market potential, as these products are widely favored across different segments of society. However, in practice, many MSMEs still encounter challenges in recording raw materials, managing inventory, and planning production, which are commonly carried out manually. Such conditions often lead to inaccurate inventory data, shortages or surpluses of raw materials, and consequently, production disruptions and material waste. These issues highlight the urgent need for a more structured and integrated system to support production management.This study aims to develop a web-based production information system designed to optimize raw material planning through the Material Requirement Planning (MRP) method. MRP was chosen as it enables optimal calculation of raw material needs based on production schedules, demand data, and procurement lead times. The system was developed using the Waterfall model, consisting of requirements analysis, system design, implementation, testing, and maintenance phases. PHP was employed as the programming language, while MySQL was used as the database management system.The resulting system is capable of providing real-time inventory recording, generating accurate estimations of raw material requirements, and producing comprehensive reports on production and inventory that serve as a valuable basis for managerial decision-making. The implementation of this system is expected to help cassava chips MSMEs improve production efficiency, minimize material waste, and reduce the risk of production delays. Overall, this research contributes a practical and applicable technological solution to support MSMEs in overcoming production management challenges in the digital era.